Dynamic Expression Changes in the Transcriptome of the Prefrontal Cortex after Repeated Exposure to Cocaine in Mice - Li, Mingzhen; Xu, Peng; Xu, Yanhua; Teng, Huajing; Tian, Weiping; Du, Quansheng; Zhao, Mei (Frontiers in Pharmacology, 2017)
ABSTRACT Prefrontal cortex (PFC)-dependent functions, such as executive function, explicit learning, and memory, are negatively affected in cocaine abusers and experimental animal models of cocaine treatment. However, its molecular mechanisms are less understood. In the present study, we performed transcriptome profiling of the dynamic changes in the PFC after repeated cocaine administration in mice. We found 463, 14, and 535 differentially expressed genes (DEGs) at 2 h, 24 h, and 7 days respectively, after the withdrawal of chronic cocaine treatment. Time-series correlation analysis identified 5 clusters of statistically significant expression patterns. The expression levels of DEGs in Clusters 1 and 5 exhibited a gradual or fluctuant decrease，Cluster 2 exhibited an initial increase followed by a decrease or return to the baseline level, and Clusters 3 and 4 exhibited a fluctuant increase in the expression of DEGs. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that genes related to oxidative phosphorylation, ribosomes, and neurodegenerative disorder were enriched in Cluster 1; genes related to the mitogen activated protein kinase (MAPK), transforming growth factor (TGF)-β, insulin signaling, and circadian pathways were enriched in Cluster 2; genes related to plasticity-related pathways were enriched in Clusters 3 and 4; and genes related to the proteasome were enriched in Cluster 5. Our results suggest that maladaptive neural plasticity associated with psychostimulant dependence may be an ongoing degenerative process with dynamic changes in the gene network at different stages of withdrawal. Furthermore, it could be helpful to develop new therapeutic approaches according to different periods of abstinence.